1983
DOI: 10.2172/5786790
|View full text |Cite
|
Sign up to set email alerts
|

Measures of risk importance and their applications. [PWR; BWR]

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, or any of their employees, makes any warranty, expressed or implied, or assumes any legal liability of responsibility for any third party's use, or the results of such use, of any information, apparatus, product or process disclosed in this report, or represents that its use by such third party would not infringe privately owned rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…HRA is an important part of PRA, and considers such performance-shaping factors as stress level, crew resources, cues, and timing. Importance analysis is typically performed on the results of a PRA and provides a quantitative perspective on risk and sensitivity of risk to changes in input values (Vesely et al 1983). Three commonly encountered importance analyses are determination of risk achievement worth (RAW), risk reduction worth (RRW), and Fussell-Vesely (F-V).…”
Section: Probabilistic Risk Assessmentmentioning
confidence: 99%
“…HRA is an important part of PRA, and considers such performance-shaping factors as stress level, crew resources, cues, and timing. Importance analysis is typically performed on the results of a PRA and provides a quantitative perspective on risk and sensitivity of risk to changes in input values (Vesely et al 1983). Three commonly encountered importance analyses are determination of risk achievement worth (RAW), risk reduction worth (RRW), and Fussell-Vesely (F-V).…”
Section: Probabilistic Risk Assessmentmentioning
confidence: 99%
“…There are many methods to estimate importance measures to identify top significant events in a system [57][58][59][60]. In this study, we used three renowned importance measures as shown in Table 1.…”
Section: Importance Measure Matricesmentioning
confidence: 99%
“…To represent the cloud information, a definition called cloud-obscuring time window (CTW) [19] is used. It refers to the time period that the target is obscured by clouds.…”
Section: Reliability Comparisonmentioning
confidence: 99%